Teachers’ Perception and Challenges of Using ICT in Teaching Mathematics at Secondary Level - Adhikari, Ganesh Prasad (Mathematics Education Forum Chitwan, 2021)
The main objectives of this study were to identify the teachers’ perceptions and challenges of using ICT tools in the mathematics classroom at the secondary level in Kathmandu. The major tool of the study was a closed-ended questionnaire consisting of 19 items. The quantitative descriptive survey design was used in this study. The researcher selected 158 teachers by using simple random method from 261 government teachers who teach compulsory mathematics at grade X of Kathmandu district in Nepal. The standardized questionnaire was administered to the sample teachers. The SPSS-25 version database was used to analyze and interpret the collected data. Teachers’ perception of using ICTs in the mathematics classroom was positive with insignificant difference in terms of gender. There were some challenges: lack of knowledge, confidence, enough experience, training, interest and access to ICT tools, lack of technical support, lack of genuine ICT Software and unstable and unreliable internet connection at the schools. Due to these challenges, teachers did not use ICT in the classroom. Therefore, teachers should learn more to improve their knowledge and skills in ICT. The government should focus on management strategies and policies to reduce the challenges faced by teachers in mathematics classrooms. By these policies, they can use the ICT tools in the classroom.